2015
DOI: 10.4141/cjas-2014-148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rumen degradable energy supplementation on forage utilization and performance of steers grazing stockpiled cool season perennial grass pastures

Abstract: . 2015. Effect of rumen degradable energy supplementation on forage utilization and performance of steers grazing stockpiled cool season perennial grass pastures. Can. J. Anim. Sci. 95: 255Á265. The objective of this study was to evaluate the effects of supplementing rumen degradable energy using blended by-product pellets that differed in starch and degradable fiber content on forage utilization and performance of steers grazing stockpiled cool-season perennial grass (CSPG) pastures. Forty-five yearling cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Legume-MBG or RWR in the current study, with greater IVOMD values than July HBG at SWIFT, indicated that MBG similar to RWR maintains its leaves and quality late in the season [17]. As forages mature, the nutritive value of both annual and perennial species declines [53] due to decreased protein and digestibility and increased fiber, which was evident in the current study.…”
Section: Forage Nutritive Valuesupporting
confidence: 53%
See 1 more Smart Citation
“…Legume-MBG or RWR in the current study, with greater IVOMD values than July HBG at SWIFT, indicated that MBG similar to RWR maintains its leaves and quality late in the season [17]. As forages mature, the nutritive value of both annual and perennial species declines [53] due to decreased protein and digestibility and increased fiber, which was evident in the current study.…”
Section: Forage Nutritive Valuesupporting
confidence: 53%
“…Allowing standing forage to accumulate for grazing at a later period, often for fall and winter grazing after dormancy is considered stockpiling. Stockpiling relies on mature forages that may not meet nutrient requirements of beef cattle [51][52][53]. According to NASEM [54], the CP and TDN requirements for mature cows and heifers either pregnant or lactating ranges from 62 to 129 g kg −1 and 449 to 645 g kg −1 , respectively.…”
Section: Forage Nutritive Valuementioning
confidence: 99%
“…Nutritive value, yield, and the overall success of stockpile grazing are dictated by forage species, length of the growing season, and soil nutrient management. As plants mature over the growing season, the nutritive value of both annual and perennial forage declines (Beck et al 2006;Biligetu et al 2014;Añez-Osuna et al 2015) as a result of a simultaneous decrease in CP and increase in neutral detergent fibre (NDF) concentrations and decrease in fibre digestibility. As a consequence of the decreased forage quality, stockpile grazing has traditionally been used primarily for beef cows in mid-gestation.…”
Section: Stockpile Grazing Of Standing Foragementioning
confidence: 99%
“…As a consequence of the decreased forage quality, stockpile grazing has traditionally been used primarily for beef cows in mid-gestation. Añez-Osuna et al (2015) observed a decrease in both CP content (from 9.9% to 6.9%) and digestible energy [2.6 to 2.2 Mcal kg −1 dry matter(DM)] in a wheatgrass-dominant [Agropyron cristatum (L.) Gaertn.] sward over a 70-d growing period from August to mid-October.…”
Section: Stockpile Grazing Of Standing Foragementioning
confidence: 99%
“…Examples include oilseeds such as off-grade canola seed and flaxseed, which are high in monounsaturated fatty acids (MUFA) and PUFA, respectively. Research has shown that relative to conventional feed sources, inclusion of these by-products in the form of blended pelleted feeds has resulted in equal or superior performance of growing cattle (Zenobi et al, 2014;Añez-Osuna et al, 2015). Such high-fat by-product feeds may also be viable supplements for gestating beef cows to meet pregnancy requirements and could potentially improve the prenatal and postnatal growth of progeny through developmental programming mechanisms.…”
Section: Introductionmentioning
confidence: 99%